The use of potentially inappropriate medications and changes in quality of life among older nursing home residents - Al Aqqad S MH; Chen LL; Shafie AA; Hassali MA; Tangiisuran B (Clinical Interventions in Aging, 2014)
Sana’ MH Al Aqqad, Li Li Chen, Asrul Akmal Shafie, Mohamed Azmi Hassali, Balamurugan Tangiisuran Pharmacy Practice Research Group, School of Pharmaceutical Sciences, Universiti Sains Malaysia, Penang, Malaysia Background: Nursing home residents are mainly older people with multiple diseases and taking multiple medications. The quality use of medication and its association with health related quality of life (HRQoL) have not been reported in Malaysia. This study aims to investigate the association between the use of potentially inappropriate medications (PIMs) and the changes observed in the HRQoL among older nursing home residents. Methods: A prospective follow up study was conducted at four nongovernmental organization nursing homes in Penang, Malaysia. Older residents (≥65 years old) taking at least one prescribed medication were included. Residents with PIMs were identified by using Screening Tool of Older Person's potentially inappropriate Prescriptions (STOPP) criteria. HRQoL was assessed using EuroQol-5 dimension (EQ-5D) and EuroQol-visual analog scale (EQ-VAS) at baseline and after a 3-month follow up. The association of PIMs with HRQoL was analyzed using Mann-Whitney U test. Results: The median age of the 211 participants was 77 years (interquartile range 72–82 years) and the median number of prescription medicines was four (interquartile range three to six). The prevalence of PIMs was 23.7% and 18.6% at baseline and 3 months later, respectively. The most commonly prescribed PIMs in decreasing order were first generation antihistamine, prescriptions of duplicate drug class, glibenclamide with type 2 diabetes mellitus, and anticholinergic to treat extrapyramidal side effects of neuroleptic medications. At baseline, there was no significant difference among residents with or without PIMs in each bracket of EQ-5D, EQ-5D index, or EQ-VAS scores. Comparison of the differences in the mean score index of EQ-5D between baseline and after 3 months also showed no statistically significant differences. Conclusion: PIMs were found to be relatively common among older nursing home residents. However, no significant changes were observed in HRQoL among these residents. Further studies with a bigger sample size and longer follow up period are required to establish this association. Keywords: elderly, health related quality of life, patient safety